Lecture notes on Clinical Pharmacology - Reid, John L.; Rubin, Peter C.;Whiting, Brian (Singapore : PG Publishing Pte, LTD., 1985)
Clinical pharmacology is a new and rapidly expanding specialty which has grown in importance with the increase in both the number and the complexity of drugs.
Section 1. Principles of clinical pharmacology -- Section 2. Cardiac arrhythmias -- Section 3. Self Poisoning.
Includes bibliographical references and index.
Keywords: DRUGS